Riyadhah: The model of the character education based on sufistic counseling - Agus Samsul Bassar; Aan Hasanah (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2020)
The purpose of education did not only build intelligent people, but also built a strong character and noble character based on the noble values of the nation and religion. Then, a quality and holistic character education becomes a necessity for the Indonesian people who want to develop the potential of the nations to have spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by themselves, society, nation and state. Character education in Islam is a moral education which is the essence of Islamic teachings. For example, the character education applied by the Sufis with various riyadhah in their zawiyah or ribath under the guidance of the murshid who becomes a role model in the process of habituating and disciplining students. This study aimed to explore the model of the character education based on sufistic counseling with the various riyadhah in guiding students to have noble character. This descriptive study used a qualitative approach by a literature study and case study in the field. The research found that the process of character internalization carried out through various riyadhah is a spiritual practice covering all aspects of life, both worship and muamalah in an effort to maintain a harmonious relationship between humans and Allah, humans with other humans, humans with their environment, and humans with themselves. Therefore, it is be able to clean the spirit and to devote themselves to the Divine, by having character or noble character and always doing good in life. Tujuan Pendidikan selain membentuk insan cerdas, juga membentuk karakter kuat dan akhlak mulia yang berpedoman kepada nilai-nilai luhur bangsa dan agama. Maka pendidikan karakter yang bermutu dan holistik menjadi sebuah keniscayaan bagi bangsa Indonesia yang ingin mengembangkan potensi diri anak bangsa agar memiliki kekuatan spiritual keagamaan, pengendalian diri, kepribadian, kecerdasan, akhlak mulia, serta keterampilan yang diperlukan dirinya, masyarakat, bangsa dan Negara.Pendidikan karakter dalam Islam adalah pendidikan akhlak yang menjadi esensi ajaran Islam. Diantara pendidikan karakter adalah yang dilakukan para sufi dengan berbagai riyadhah di zawiyah atau ribath mereka dibawah bimbingan guru mursyid yang menjadi role model dan teladan dalam proses pembiasaan dan pembinaan disiplin para murid. Penelitian ini bertujuan untuk menggali model pendidikan karakter berbasis konseling sufistik melalui berbagai riyadhah dalam membimbing para murid agar memiliki karakter atau akhlak mulia.Penelitian deskriptif ini menggunakan pendekatan kualitatif dengan mengadakan Studi Kepustakaan dan studi kasus di lapangan. Penelitian menemukan bahwa Proses internalisasi karakter yang dilakukan melalui berbagai riyadhah, merupakan latihan spiritual mencakup seluruh aspek kehidupan, baik ibadah maupun muamalah dalam upaya menjaga hubungan harmonis manusia dengan Allah, manusia dengan manusia lain, manusia dengan lingkunganny, dan manusia dengan dirinya sendiri. Sehingga mampu membersihkan ruhani dan mampu mengabdikan diri kepada Ilahi, dengan memiliki karakter atau akhlak mulia dan senantiasa melakukan kebaikan dalam hidup.